Cardiotoxicity of polystyrene nanoplastics and associated mechanism of myocardial cell injury in mice - Ziyi Xiong; Qiling Kong; Juan Hua; Qi Chen; Dandan Wang (Ecotoxicology and Environmental Safety)
Aims: Nanoplastics (NPs) are emerging organic pollutants generated by plastic degradation and are ubiquitous in the environment. They can be accumulated through the food webs and enter the human body through dietary intake, posing health risks. The main target organs of NP accumulation are the lungs, liver, heart, and kidneys. However, compared with that for other target organs, research on the adverse effects of NPs on the heart is limited. We aimed to investigate the toxic effects of polystyrene NPs on the heart and the associated mechanisms. Methods and results: Forty-eight male C57BL/6 mice were randomly divided into control and experimental groups. Three experimental groups were exposed to NP doses of 30, 60, and 100 mg/L for 42 days. The mice exhibited enlarged ventricular chambers, thinned ventricular walls, decreased ejection fraction, reduced heart rate, and lowered blood pressure with increasing PS-NP concentration. In vitro experiments using H9C2 myocardial cells demonstrated that PS-NPs activate the TNF-α/NF-κB and P38/MAPK signaling pathways and thereby induce inflammatory infiltration and oxidative stress. This can lead to myocardial fibrosis and apoptosis and thus eccentric cardiac hypertrophy and impaired contractile function. Conclusions: This study provides new evidence regarding the potential mechanisms of PS-NP cardiovascular toxicity as well as insights into the diagnosis and treatment of unexplained dilated cardiomyopathy in clinical settings.